The Potential of Andrographis paniculata as a Supplement for the Management of Benign Prostate Hypertrophy (BPH): A Systematic Literature Review - Amal, Rizki Jaya; Irfansyah (HM Publisher, 2023)
Andrographis paniculata has been studied for their potential protective action on benign prostate hypertrophy (BPH). This polyphenol has been reported to repair the antioxidant defense mechanisms in the prostate, reduce inflammation, and inhibit IGF-I and IGF-II. Andrographis paniculata has been studied for its potential protective action on benign prostate hypertrophy (BPH) and its ability to reduce inflammation in the prostate. This study aimed to explore various scientific evidence related to the exploration of the potential of Andrographis paniculata in the management of benign prostate hypertrophy (BPH). These three studies consistently present data demonstrating the superiority of andrographolide isolate in the apoptosis initiation of prostate cells. Increased apoptosis of prostate cells is believed to cause a decrease in the mass of prostate tissues and organs. The decrease in prostate mass will relieve pressure on the urethral canal and will eliminate complaints of difficulty urinating in patients with BPH. In conclusion, Andrographis paniculata has the potential to supplementation in the management of benign prostate hypertrophy through regulation of prostate cell apoptosis initiation.